Senses and meanings on education and work in young technical high school students; Hualpén, Concepción - Ganter Solís, Rodrigo; Tornel Cifuentes, Mabel (Última Década, 2019)
This article is a result of the insight gained from a research on the future expectations of young technical high school students and the meanings they give to education and work in their future plans. The main conceptual axis of this research is the new trend of youth studies, which is based on the articulation of multiple factors renewing and transforming the experience of being young.The results show a standardization of expectations and future plans in those students whose family histories of scarcity have related, in a direct way, their future aspirations of a “better life” to economic needs, counting on education and work as their main tools to achieve it.